The Study of Consumer Behavior Towards Snakehead Menu (Channa striata) in Culinary Tour Kampung Nasi Kuning in the City of Samarinda (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The purpose of this study was to know the consumer characteristics in buying indonesian yellow rice with the menu of snakehead fish, to know the relation between buying decision with price perception, location perception, and taste perception, and to identify level of consumer satisfaction reviewed from aspect of product, price, location, and also service. This research is conducted on (November 2015 - June 2016) by using sampling methods that is Accidental sampling.The result of the research shows that consumers characteristic that buy indonesian yellow rice with the menu of snakehead fish in the Culinary Tour Area Kampung Nasi Kuning Kota Samarinda is dominated by female consumer (50,91%), age 21 – 30 (34,55%), high school educated SLTA (45,45%), working as employee (45,45%), income Rp 2.000.001 - Rp 4.000.000 (65,45%) and consumer with the tribe of Banjar stands 25 people (45,45%).Consumer perception concerning the price, location, and taste toward the buying decision is categorized as an average consideration. The result of the analysis of correlation coefficients Rank spearman that means there is a relation between buying decision toward price perception, location perception, and taste perception in indonesian yellow rice in the Culinary Tour Area Kampung Nasi Kuning Kota Samarinda.The satisfaction index of consumer the product is categorized as high satisfaction around 76,4%, price is categorized as high satisfaction around 68,8%, location is categorized as average satisfaction around 66% and service is categorized as average satisfaction around 67%.